Paraganglioma of the Tongue in a Chow Chow Dog: A Comparison With the Human Counterpart and Literature Review - Rodrigues, Fábio Ranyeri Nunes; da Silva Freire, Jeniffer Mendes; Fidelis, Luana de Aguiar Paes; Pereira, Alexandra Ariadne Bittencourt Gonçalves; de Sousa, Davi Emanuel Ribeiro; Wilson, Tais Meziara; Soto-Blanco, Benito; de Castro, Márcio Botelho (Frontiers in Veterinary Science, 2020)
Over the last 20 years, substantial knowledge has been developed in Veterinary oncology, and tumors previously reported only in humans have been identified in animals. Primary paragangliomas of the tongue are extremely rare tumors in human beings and have never been reported in animals. A Chow-Chow dog showed an ulcerated nodule at the lingual body, deeply infiltrated, which extended to the base of the tongue. A full clinical and pathological investigation was conducted, and a post-surgical follow-up of 6 months did not detect recurrence. Cytological, histological, and immunohistochemical features are presented and support the diagnosis of lingual paraganglioma. The paraganglioma of the tongue reported in this Chow Chow dog shares many similarities with the human counterpart.